THE ROLE OF THE INTERNAL AUDITOR IN APPLYING FINANCIAL PERFORMANCE INDICATORS TO IMPROVE BANKING PERFORMANCE APPLIED RESEARCH: IN (MIDDLE EAST BANK, ASHUR INTERNATIONAL BANK, KHALEEJI COMMERCIAL BANK) - Fadil Hussein Abbas (Scholar Express Journals, 2022)
The research aims to provide an introductory framework for the internal auditor in applying the banking financial performance indicators to the research sample, measuring the banking financial performance indicators to determining the strengths and weaknesses in the banking performance. By addressing the main research problem that revolves around the following questions :Does the internal auditor apply the banking financial performance indicators to the research sample? Does the application of banking performance indicators have an impact on improving banking performance? The research reached the most important conclusions Ashur International Bank outperforms in the rate of return on assets (ROA), which gives it an advantage over the Gulf Commercial Bank and the Middle East Bank in achieving net profits from asset investments. The Ashur International Bank also outperformed the rate of return on equity (ROE), which gives it preference over Khaleeji Commercial Bank and the Middle East Bank in the efficiency of management in exploiting the bank's own money and the ability of this money to generate profit. Among the most important recommendations are The necessity for the Gulf Commercial Bank and the Middle East Bank to enhance the rate of return on assets (ROA), by realizing net profits from investments in current assets. And the necessity for the Gulf Commercial Bank and the Middle East Bank to enhance the rate of return on equity (ROE) by exploiting the bank's own money and the ability of this money to generate profit
Keywords: Internal auditor; financial performance; Indicators banking performance